Economic Burden of HIV/AIDS upon Households in Nepal: A Critical Review - Poudel, Ak Narayan; Newlands, David; Simkhada, Padam (Nepal Journal of Epidemiology, 2015)
Thousands of people are infected with HIV/AIDS in Nepal and most of them are adults of working age. Therefore, HIV/AIDS is a big burden in Nepal. This review was conducted to find the existing knowledge gap about the economic burden of HIV/AIDS at the household level in Nepal, the extent of economic burden exerted by the disease, and to provide policy recommendations. It is concluded that there was a considerable knowledge gap about the issue, and the economic burden exerted by HIV/AIDS was big enough to push the affected households into poverty. It is suggested that more studies need to be conducted to fill the knowledge gap. Similarly, Government of Nepal and other organisations working in the field of HIV/AIDS need to provide economic supports (e.g.- support for travel costs) to the HIV positive people and need to increase the awareness level among general population for reducing stigma and discrimination, and reducing economic burden on them.